1994
DOI: 10.1139/y94-175
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of sarcoplasmic reticulum Ca2+-sequestering function in homogenates of different fibre type composition following sprint activity

Abstract: To examine the effect of exercise on sarcoplasmic reticulum function in muscle tissue of different fibre composition, adult male Wistar rats weighing 388 ± 23 g (x ± SE) ran intermittently on a treadmill until fatigue. Fatigue was induced by 15–20 min of running performed at 52 m/min on an 8° incline in periods of 2.5 min of exercise separated by 2 min of recovery. Analysis of sarcoplasmic reticulum Ca2+ ATPase activity determined in homogenates indicated no difference (p > 0.05) between age-matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
1
9
1
Order By: Relevance
“…The effects of exercise on SR function is not as clear with other species. Measurements of Ca 2+ -uptake and Ca 2+ -ATPase activity on whole muscle homogenates, using procedures similar to that employed with humans, were not altered in rat soleus or gastrocnemius either by prolonged running (Chin & Green 1996) or sprinting (Dossett-Mercer et al 1994). However, reductions in Ca 2+ -sequestration function have been reported with exercise, both following prolonged (Byrd et al 1989a, Belcastro et al 1993) and sprint (Byrd et al 1989b) running in highly enriched SR fractions.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The effects of exercise on SR function is not as clear with other species. Measurements of Ca 2+ -uptake and Ca 2+ -ATPase activity on whole muscle homogenates, using procedures similar to that employed with humans, were not altered in rat soleus or gastrocnemius either by prolonged running (Chin & Green 1996) or sprinting (Dossett-Mercer et al 1994). However, reductions in Ca 2+ -sequestration function have been reported with exercise, both following prolonged (Byrd et al 1989a, Belcastro et al 1993) and sprint (Byrd et al 1989b) running in highly enriched SR fractions.…”
Section: Discussionmentioning
confidence: 85%
“…All individual values are based on the average of two duplicates performed on a single sample, calculated from the initial linear portion of the reaction time curve. Details of these procedures have previously been published by our group (Chin & Green 1996, Dossett-Mercer et al 1994. As a result of an insuf®cient database Ca 2+ -ATPase during exercise are only provided for 0, 7 and 12 weeks of training.…”
Section: Analytical Proceduresmentioning
confidence: 99%
“…However, we did not observe an effect on SR vesicle Ca 2+ uptake rate following exercise in the arm. When viewed as a whole, most studies have reported a reduced SR vesicle Ca 2+ uptake following exercise (Luckin et al 1991; Duhamel et al 2006 a ), though SR Ca 2+ uptake has also been reported to be unaltered (Dossett‐Mercer et al 1994, 1995). These discrepancies may be related to the exercise mode and training status.…”
Section: Discussionmentioning
confidence: 99%
“…Although most investigations indicate a decline of the SR Ca 2+ transport by exercise, some investigators found no alterations. Ca 2+ ATPase and Ca 2T uptake of rat soleus and gastrocnemius homogenates were unaffected by intermittent running (DOSSETT-MERCER et al, 1994). A short term Stimulation elicited no change in Ca 2+ uptake in white or red rat gastrocnemius tissues but increased Ca 2+ ATPase activity in white gastrocnemius tissues .…”
Section: Introductionmentioning
confidence: 79%